Revista O Cruzeiro: Alceu Penna e os figurinos de moda - Fernandes, Rosane Schmitz (2009)
This dissertation refers the research, which covers the areas of discursive semiotics, communication and fashion, having as its universe the set of Alceu Penna s fashion plates, in the magazines O Cruzeiro, within the column Figurinos, in the 1950 s decade. The corpus of this research was built out of this set of images, enabling the construction of the social practices visibility issue, referring to a certain female simulacrum and type of women, inserted in the image universe of the magazine. Thus, the research revolves around the questions: What kind of Brazilian woman simulacrum Alceu Penna proposed through O Cruzeiro magazine? How did he construct this simulacrum in the fashion drawings in the magazine? This way, the research seeks to identify and analyze the fashion images proposed by the designer as its general goal. Such images signal female features that will anchor the construction of a Brazilian woman simulacrum. For the specific goals the research seeks to achieve the following: 1) Present the female way(s) of dressing conveyed in Alceu Penna s column called Figurinos; 2) Contribute for the identification of the Brazilian woman in the 1950 s decade; 3) Verify existing conceptual relations between fashion, woman simulacrum and the culture industry represented in O Cruzeiro magazine, within the column Figurinos during that period; 4) Establish the logic in the relations between the expression categories (plastic formants) and the content categories (meaning generative course) in order to describe the type of semiosis existing between expression plan and content plan; 5) Identify correlations between the fields of fashion, advertising and economics in the magazine; 6) Contribute to fashion studies. The methodological procedures compose a descriptive and interpretative method for the analysis of verbal and visual arrangements of the text, named syncretic, which copes with the identification of mechanisms that structure internally the text in relation to the sociohistorical context. This way, the structural complexity of the text was understood, in which the relations and semiosis are produced as a whole of meaning, according to Algirdas Julien Greimas theoretical framework. Also, the sociosemiotics developed by Eric Landowski was used, highlighting the concepts of simulacrum, presence as a sense system, correlated to interaction and visibility systems. The analysis of the visual aspect of fashion plates in the column was grounded on Jean-Marie Floch s plastic and syncretic semiotics approaches. As for the visuality aspect of fashion Ana Claudia de Oliveira s statements were used, which relate it to appearance discourses. Having this accession, the semiotic analysis tested the hypothesis that Alceu Penna s fashion plates shape a slim, thin female body, with marked waist and gestures that show sometimes a relaxed, moved posture in its internal world and sometimes a formal, static and conservative one in a social environment. It was apprehended in these drawings the construction of a family woman simulacrum, who is within a dependence relation with the masculine, and a Brazilian woman simulacrum, who follows the international fashion trends and shows herself to others, besides the adoption of Brazilian culture stereotypes, in order to reveal her insertion and sense of belonging to the elites context. The drawings correlate to the advertising discourses of the magazine, that promote an economic model of consumption of goods produced by the implanted industry in the country, linked a model Brazilian social of a modern way of life, where the masculine and the feminine have support with French and New Yorker fashion matrixes